Mirabegron 50 mg once daily, long-term treatment maximizes benefit in middle-aged and older people with overactive bladder syndrome: a systematic review and meta-analysis of nine phase II/III, randomized, double-blind, parallel-design, placebo-controlled, multicenter, and multinational trials - Zhang, Xiangxiang; Mao, Yinhui; Liu, Yang; Sun, Jilei; Sun, Juntao; Pan, Chenli; Wang, Zhuo; Wei, Zhitao; Yang, Yong (Frontiers in Surgery, 2024)
The prevalence and severity of overactive bladder increases with age. Mirabegron is approved to treat the disease. This meta-analysis systematically evaluated the efficacy and safety of mirabegron compared with placebo for the treatment of overactive bladder. We searched Pubmed and the Cochrane Library (searched 30 October 2023) for relevant articles (source: MEDLINE, EMBASE, CT.gov, ICTRP, CINAHL). Randomized controlled trials in adults with overactive bladder syndrome that compared mirabegron with placebo treatment. Data were processed as described in the Cochrane Handbook for Systematic Reviews of Interventions (Review Manager [Computer program] Version 5.4). Nine trials with parallel-group designs were included (10 articles). The evaluation included a total of 8527 adults, including 6445 women and 2082 men, of whom 5726 were White, 2462 were Asian, and 161 were Black. The mean age of the participants ranged from 53.4 to 60.3 years. This evaluation involved three specifications of mirabegron: 25mg, 50mg, and 100mg. In all trials, patients were enrolled in a 12-week double-blind treatment period, and the dose was once daily.The review of trials found that on average, people taking mirabegron had about thirteen ml more volume voided per micturition, five fewer micturitions, and four fewer incontinence episodes every week, with moderate improvements in quality of life. About one in five people taking the drug reported TRAEs. Mirabegron treatment is well tolerated, and the risk of adverse events is similar to placebo. For best results, it is best to stick to 50 mg once daily for a long period of time. It is not clear whether any benefits are sustained after treatment stops.